A multi-band spectrum sensing method based on sticky hidden Markov model - Zhongjie JIA; Ming JIN; Xiaoqun SONG (Dianxin kexue)
Existing multi-band spectrum sensing methods often use the sparsity of broadband spectrum.However, high spectrum occupancy rate of primary users degrades their performance severely.To address this issue, a novel multi-band spectrum sensing method was proposed by exploiting the state correlation among adjacent frequency bands.Firstly, a sticky hidden Markov model (SHMM) was established by regarding the multi-band states and measured energies as hidden and observed variables.In the SHMM, a sticky factor was introduced to represent the state correlation among adjacent frequency bands.Secondly, iterative expressions for the parameters of SHMM were derived.Finally, multi-band spectrum sensing was implemented by obtaining the posterior mean of observations from every frequency bands.Simulation results show that the proposed method outperforms existing methods, and when the false alarm probability is 0.1, the average frequency band occupancy rate is 50%, and the average signal-to-noise ratio is -12 dB, the detection probability can reach close to 0.99, which is about 30% higher than the detection probability of other methods.In addition, the proposed method had a faster convergence rate than existing methods and therefore has lower computational complexity.